Development of a set of mobile phone text messages designed for prevention of recurrent cardiovascular events. (29th August 2020) - Redfern, J; Thiagalingam, A; Jan, S; Whittaker, R; Hackett, ML; Mooney, J; Keizer, L De; Hillis, GS; Chow, CK
Abstract: Background: Supporting lifestyle change is an effective way of preventing recurrent events in people with cardiovascular disease (CVD). However, there is a need to develop innovative strategies that increase access to programmes for individuals at high risk of CVD. This study aimed to develop a bank of text messages designed to provide advice, motivation, and support for decreasing cardiovascular risk. Design: Iterative development process with mixed methods Methods: An initial bank of 120 text messages was drafted based on behaviour change techniques, guidelines, and input from clinicians and public health experts. A questionnaire was then administered to participants ( n  = 53) for evaluation of message content, usefulness, and language. To test the process of delivery, a pilot study was conducted using a specifically designed computer programme that delivered messages to multiple mobile phones according to a pre-specified schedule. Data were collected regarding message timing, delivery, and usefulness. Results: In the qualitative questionnaire, 92% of participants found the messages easy to understand and 86% found the messages contained useful information. Positive feedback was also obtained from the pilot study. Based on these results, together with suggestions provided, several messages were reworded and an additional 44 were written. The need for semi-personalization was also identified and a random set of 103 individualized messages was created. Conclusions: A final bank of 137 mobile telephone text messages designed to support behaviour change and decrease cardiovascular risk have been developed through a multistep iterative process. This provides a scientific approach for future developers of health-related text messages.